Pengujian Aplikasi E-learning Berbasis Web Di SMP Swasta Al-Hasaniyah - Ahmad Fajri; Moh. Ridzki Alif Maulana; Nazila Iva Sugianisa; Rio Ardy Milala; Aries Saifudin (CV. Multi Kreasi Media, 2022)
The corona virus has hit various parts of the world and it disrupts and paralyzes the activities of learning activities of a private junior high school Al-Hasaniyah, technological advances cannot be denied anywhere because the school already has internet access and computerized device facilities, but still does not have website media in the form of E-Learning learning facilities or learning online without face-to-face. So the researcher made an application and conducted a special test of the Black Box method on the E-learning application, by achieving the results expected by the tester.